Polygenic Risk Variants for Type 2 Diabetes Susceptibility Modify Age at Diagnosis in Monogenic HNF1A Diabetes - Lango Allen, Hana (American Diabetes Association, 2010)
OBJECTIVE: Mutations in the HNF1A gene are the most common cause of maturity-onset diabetes of the young (MODY). There is a substantial variation in the age at diabetes diagnosis, even within families where diabetes is caused by the same mutation. We investigated the hypothesis that common polygenic variants that predispose to type 2 diabetes might account for the difference in age at diagnosis. RESEARCH DESIGN AND METHODS: Fifteen robustly associated type 2 diabetes variants were successfully genotyped in 410 individuals from 203 HNF1A-MODY families, from two study centers in the U.K. and Norway. We assessed their effect on the age at diagnosis both individually and in a combined genetic score by summing the number of type 2 diabetes risk alleles carried by each patient. RESULTS: We confirmed the effects of environmental and genetic factors known to modify the age at HNF1A-MODY diagnosis, namely intrauterine hyperglycemia (−5.1 years if present, P = 1.6 × 10(−10)) and HNF1A mutation position (−5.2 years if at least two isoforms affected, P = 1.8 × 10(−2)). Additionally, our data showed strong effects of sex (females diagnosed 3.0 years earlier, P = 6.0 × 10(−4)) and age at study (0.3 years later diagnosis per year increase in age, P = 4.7 × 10(−38)). There were no strong individual single nucleotide polymorphism effects; however, in the combined genetic score model, each additional risk allele was associated with 0.35 years earlier diabetes diagnosis (P = 5.1 × 10(−3)). CONCLUSIONS: We show that type 2 diabetes risk variants of modest effect sizes reduce the age at diagnosis in HNF1A-MODY. This is one of the first studies to demonstrate that clinical characteristics of a monogenic disease can be modified by common polygenic variants.